Serum vitamin D levels during activation and remission periods of patients with juvenile idiopathic arthritis and familial Mediterranean fever - Dağdeviren-Çakır, Aydilek; Arvas, Ahmet; Barut, Kenan; Gür, Emel; Kasapçopur, Özgür (The Turkish Journal of Pediatrics, 2016)
The aim of this study was to determine the frequency of vitamin D deficiency and/or insufficiency in children with juvenile idiopathic arthritis (JIA) and familial Mediterranean fever (FMF) and to assess the relationship between vitamin D and disease activity. Sixty four patients with JIA, thirty six patients with FMF and one hundred healthy children were enrolled in this study. Vitamin D levels were measured during activation and remission periods in the patients with JIA and during attack and attack free periods in the patients with FMF. The mean vitamin D levels were found to be 18. 9±11 ng/ml and 18.6±9.2 ng/ml during activation and remission periods of disease, respectively, in the patients with JIA, 16±8.5 ng/ml and 13.1±6.4 ng/ml during attack and attack-free periods, respectively, in the patients with FMF and 26.7±10.5 ng/ml in the healthy children. There was no significant difference between vitamin D levels during activation and remission periods in the patients with JIA, whereas vitamin D levels during attack free periods were lower compared to attack periods in the patients with FMF. No significant relationship was found between disease activity and serum vitamin D levels. The vitamin D levels of the children with JIA and FMF were significantly lower compared to the healthy children. The frequency of vitamin D deficiency and insufficiency was considerably high among the patients with JIA and FMF.
Keywords: children; disease activity; familial Mediterranean fever; juvenile idiopathic arthrtitis; vitamin D